Effect of dietary protein quality and rumen protected amino acid supplementation on performance and carcass characteristics of feedlot cattle. - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2022)
Dissertation (MSc (Agric) Animal Science: Animal Nutrition)--University of Pretoria, 2022.